2021
DOI: 10.3389/fimmu.2021.745625
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T4 Vaccine Platform for Next-Generation Influenza Vaccine Development

Abstract: Developing influenza vaccines that protect against a broad range of viruses is a global health priority. Several conserved viral proteins or domains have been identified as promising targets for such vaccine development. However, none of the targets is sufficiently immunogenic to elicit complete protection, and vaccine platforms that can enhance immunogenicity and deliver multiple antigens are desperately needed. Here, we report proof-of-concept studies for the development of next-generation influenza vaccines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…In the study by Ortega-Rivera et al, mice immunized with Qβ conjugated with the S protein peptides TESNKKFLPFQQFGRDIA, PSKPSKRSFIEDLLFNKV, HADQLTPTWRVY produced high-level IgG antibodies, while animals vaccinated with free S protein peptides did not [ 47 ]. Li and colleagues found that whereas the proteins of influenza virus 3M2e displayed on T4 nanoparticles, without any adjuvant, elicited extremely high-levels of 3M2e-specific IgG antibodies, 3M2e conjugated to RB69 Soc induced low levels of 3M2e-specific IgG antibodies [ 38 ]. In addition, the 58 amino acid peptide of the Pfs47 antigen of P. falciparum conjugated phage AP205 VLP was more immunogenic than unconjugated Pfs47 monomers, inducing a high level of antibodies [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Ortega-Rivera et al, mice immunized with Qβ conjugated with the S protein peptides TESNKKFLPFQQFGRDIA, PSKPSKRSFIEDLLFNKV, HADQLTPTWRVY produced high-level IgG antibodies, while animals vaccinated with free S protein peptides did not [ 47 ]. Li and colleagues found that whereas the proteins of influenza virus 3M2e displayed on T4 nanoparticles, without any adjuvant, elicited extremely high-levels of 3M2e-specific IgG antibodies, 3M2e conjugated to RB69 Soc induced low levels of 3M2e-specific IgG antibodies [ 38 ]. In addition, the 58 amino acid peptide of the Pfs47 antigen of P. falciparum conjugated phage AP205 VLP was more immunogenic than unconjugated Pfs47 monomers, inducing a high level of antibodies [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, further studies are needed to address this point. Human clinical trials and hundreds of T4 phage vaccine immunizations over the years involving mice, rats, rabbits, and macaque animal models and diverse antigens such as anthrax, plague, and HIV did not identify any significant side effects ( 72 75 ). Furthermore, the T4 phage is one of the most stable virus scaffolds known ( 48 ), and our stability studies showed that the T4-CoV-2 vaccine was completely stable at an ambient temperature for at least 10 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As VLPs directly mimic native viruses, these nanoparticle systems can induce strong, T-independent stimulation of B cells through BCR crosslinking ( Bachmann et al, 1993 ; Fries et al, 2021 ). VLPs also contain viral PAMPs, such as nucleic acids, that help activate, in many cases, and an adjuvant-free protective immune response ( Venter et al, 2011 ; Li M. et al, 2021 ; Ortega-Rivera et al, 2021 ; Royal et al, 2021 ; Warner and Frietze, 2021 ). Additionally, if they are made in bacteria, VLPs may contain some bacterial components that further promote a protective response without use of classical alum adjuvants ( Mohsen et al, 2021 , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MS2-L2 VLPs were protective against all tested viral strains, and one study even confirmed that the protective antibodies generated from vaccination with these VLPs last for over 9 months ( Yadav et al, 2021 ). Bacteriophage T4 have also been developed as a vaccine platform, specifically for use against influenza ( Li M. et al, 2021 ). In addition to bacteriophage, insect and plant viruses may also be genetically modified to generate chimeric viruses.…”
Section: Virus-like Particlesmentioning
confidence: 99%